The Role of Work-Life Balance in Employee Retention: A Systematic Literature Review among Millennials and Generation Z - Andi Harnas Baharuddin (PT. Anagata Sembagi Education, 2026)
Employee retention has become a critical strategic concern for organizations navigating a workforce increasingly composed of Millennials and Generation Z, two cohorts widely known for prioritizing balance between professional and personal life over traditional incentives such as salary alone. This study conducts a systematic literature review examining the role of work-life balance in shaping employee retention among these two generational cohorts. Following PRISMA 2020 guidelines, twenty-five peer-reviewed articles published between 2021 and 2026 were identified, screened, and thematically synthesized from Google Scholar, Scopus-indexed journals, and other reputable academic repositories. The review reveals that work-life balance consistently exerts a significant positive influence on employee retention, primarily through the mediating roles of job satisfaction, organizational commitment, and job embeddedness, while simultaneously reducing turnover intention. Flexible arrangements, supportive leadership, employer branding, and compensation emerge as key reinforcing mechanisms. Notable generational nuances are identified: Millennials value stability and career progression alongside balance, whereas Generation Z emphasizes autonomy, mental well-being, and purpose-driven work. This review contributes a novel integrative, generation-differentiated framework linking work-life balance to retention outcomes and offers practical implications for human resource strategies, including flexible scheduling, welfare benefits, and generation-sensitive retention programs. Limitations and future research directions are discussed.